Boosting Nigeria’s Gross Domestic Product with Digital Marketing - Ajayi, Johnson O.; Alase, Peter O.; Ilugbusi, Segun B. (ABUAD Journal of Social and Management Sciences, 2024)
The most transformative and impactful force in the global socioeconomic landscape including Nigeria is digital marketing. This study analysed the challenges, opportunities, and benefits of digital marketing in job creation in Nigeria. A descriptive survey research design was adopted. Secondary data which were collected from relevant ministries, departments, and agencies were used for the study. This study exposed the important components of digital marketing against the socioeconomic situation in the country. The study checked mobile usage, the present challenges, and opportunities for digital marketing with its impact in Nigeria. Through relevant digital campaigns, the relationship between digital marketing and job creation opportunities in Nigeria were analysed. The study confirmed that there is a great gap between the required job skills and available job skills; hence, the high rate of unemployment in the country. The study concluded that digital marketing is a good foundation for an improvement in job skills, and job employability through improved school curricula, teaching methods, and soft skills. Therefore, increased job skills will boost employment and productivity within and outside Nigeria, thereby boosting the Gross Domestic Product (GDP) in the short run and long run.